The Impact of the International Office Service Quality on Student’s Satisfaction and Loyalty The Case of EMU, Northern Cyprus - Osmanova, Irada (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Service quality, student’s satisfaction and loyalty are the main concepts that higher educational institutions (universities) must focus on if they are planning to run competitiveness and growth of the institution. Accordingly, higher educational institutions have many fields which care on service quality, students’ satisfaction and student’s loyalty. One of the most important fields of the university is the international office which recruits international students from all around the world, provides the necessary guidance and advising services. The international office’s service quality plays a significant role in satisfaction and loyalty of international students. The main purpose of this thesis is to measure a service quality of the Eastern Mediterranean University’s (EMU) international office and find out how it affects student’s satisfaction and student’s loyalty to the university. This research involved collecting data from randomly selected international students at EMU Campus, in Northern Cyprus. Survey questionnaires were distributed among 235 international students coming from different countries of the world. SERVQUAL Model, One Way ANOVA, Descriptive Statistics, Correlation, Independent Samples T-Test, Gap Analysis and Duncan Test are used to analyze the data. As a result, findings show that in respect of the international office service quality with student’s satisfaction, the expectations of international students exceed the perceptions of international students.

ÖZ: Rekabet güçlerinin artırılmasını ve büyümeyi hedef alan üniversitelerin hizmet kalitesi, öğrenci memnuniyeti ve sadakatına odaklanması gereği en önemli kavramlar olarak ortaya çıkmaktadır. Buna göre, yükseköğretim kurumlarında hizmet kalitesine, öğrenci memnuniyetine ve öğrenci sadakatına özen gösteren birçok departman vardır. Üniversitelerin en önemli departmanlarından birisi de uluslararası ofistir, dünyanın dört bir yanından uluslararası öğrencileri getirmekte, gerekli rehberlik ve danışmanlık hizmetleri vermektedir. Uluslararası ofisin hizmet kalitesi öğrenci memnuniyetinde ve öğrenci sadakatında en önemli rol oynamaktadır. Bu tezin temel amacı Doğu Akdeniz Üniversitesi (DAÜ) uluslararası ofisin hizmet kalitesini ölçmek, öğrencinin memnuniyeti ve öğrencinin üniversiteye sadakatını nasıl etkilediğini öğrenmektir. Bu araştırma Kuzey Kıbrıs'ta, DAÜ Kampüsü'nde rastgele seçilen uluslararası öğrencilerinden veri toplanması ile gerçekleştirilmiştir. Anketler dünyanın farklı ülkelerinden gelen 235 uluslararası öğrenci arasında dağıtılmıştır. Verileri analiz etmek için SERVQUAL Modeli, Tek yönlü ANOVA, tanımsal istatistikler, bağımsız t-testi, boşluk analizi ve Duncan Test verilerin analizinde kullanılmıştır. Sonuç olarak, öğrencinin memnuniyeti ile uluslararası ofisin hizmet kalitesi açısından baktığımızda, uluslararası öğrencilerin beklentileri algılarından daha yüksek olduğu görülmektedir.
Master of Business Administration in Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2016. Supervisor: Prof. Dr. Mustafa Tümer.
Keywords: Business Administration; International Office--Eastern Mediterranean University--Student's Satisfaction and Loyalty--Famagusta (Cyprus, North); Customer loyalty--Students Loyalty; Service Quality; Students Satisfaction; Students Loyalty; EMU; Northern Cyprus; International Office; SERVQUAL Model